Are There Benefits from the Use of Fish Oil Supplements in Athletes? A Systematic Review. Issue 5 (8th May 2020) - Lewis, Nathan A; Daniels, Diarmuid; Calder, Philip C; Castell, Lindy M; Pedlar, Charles R
ABSTRACT: Despite almost 25 y of fish oil supplementation (FS) research in athletes and widespread use by the athletic community, no systematic reviews of FS in athletes have been conducted. The objectives of this systematic review are to: 1 ) provide a summary of the effect of FS on the athlete's physiology, health, and performance; 2 ) report on the quality of the evidence; 3 ) document any side effects as reported in the athlete research; 4 ) discuss any risks associated with FS use; and 5 ) provide guidance for FS use and highlight gaps for future research. Electronic databases (PubMed, Embase, Web of Science, Google Scholar) were searched up until April 2019. Only randomized placebo-controlled trials (RCTs) in athletes, assessing the effect of FS on a health, physiological/biochemical, or performance variable were included. Of the 137 papers identified through searches, 32 met inclusion criteria for final analysis. Athletes varied in classification from recreational to elite, and from Olympic to professional sports. Mean age for participants was 24.9 ± 4.5 y, with 70% of RCTs in males. We report consistent effects for FS on reaction time, mood, cardiovascular dynamics in cyclists, skeletal muscle recovery, the proinflammatory cytokine TNF-α, and postexercise NO responses. No clear effects on endurance performance, lung function, muscle force, or training adaptation were evident. Methodological quality, applying the Physiotherapy Evidence Database (PEDro) scale, ranged from 6 to a maximum of 11, with only 4 RCTs reporting effect sizes. Few negative outcomes were reported. We report various effects for FS on the athlete's physiology; the most consistent findings were on the central nervous system, cardiovascular system, proinflammatory cytokines, and skeletal muscle. We provide recommendations for future research and discuss the potential risks with FS use.